Hermeneutika Versus Ta’wil (Studi Komparatif) - Ahmad Kali Akbar (Kalimah: Jurnal Studi Agama dan Pemikiran Islam, 2015)
When the term hermeneutics and ta’wil coupled, there will be a controversial opinion. Neither of the Muslims as the owner term ta’wil, or any of a group of owners of hermeneutics. Some say hermeneutics and ta’wil no different alias exactly the same, so the use of hermeneutics together with the user function ta’wil. However, others do not think so. They consider far different hermeneutics ta’wil. This difference is seen from different sides of the two. In terms, history, object of study as well as the methodology applied in interpreting a text, particularly the scriptural text. And in the Islamic world it self, hermeneutics has been recommended to become the new interpretation as a replacement method of interpretation and ta’wil method is considered old-fashioned. All that problems above is what attracted the attention of the writer to examine critically, objectively and fairly to produce conclusions which of the two groups most worthy justified. Do hermeneutics and ta’wil the same? And could it be used as a method hermeneutic interpretation of the Qur’an? Those questions will be answered in this paper is clear, straightforward and pithy and of course with all the shortcomings writer.